2022
DOI: 10.26773/mjssm.220903
|View full text |Cite
|
Sign up to set email alerts
|

Four-week whole-body vibration training and its effects on strength, power and sprint performance in young basketball players - a randomized control trial

Abstract: We aimed to investigate whether the addition of whole-body vibration (WBV) to resistance training (RT) will be more beneficial in improving lower limbs muscle strength, power and sprinting performance than RT alone in young basketball players. We recruited 30 young basketball players to participate in four weeks of training and assessments. They were randomized into the WBV resistance training group (VRTG, n=15) and a conventional resistance training group (RTG, n=15), performed 3 times per week. At the beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The three most popular methods for assessing vertical jump are the CMJ, SJ, and DJ ( Kozinc, Plesa & Sarabon, 2021 ), and it is well-known that participants can achieve higher jump heights and greater output power in the CMJ compared with the SJ ( Bobbert et al, 1996 ). A study suggested that 4 weeks of PBT did not significantly improve the CMJ and SJ of athletes ( Kovacevic et al, 2022 ). However, the results of the present study were different; after 4 weeks of training, the participants’ CMJ in the APRE group was significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…The three most popular methods for assessing vertical jump are the CMJ, SJ, and DJ ( Kozinc, Plesa & Sarabon, 2021 ), and it is well-known that participants can achieve higher jump heights and greater output power in the CMJ compared with the SJ ( Bobbert et al, 1996 ). A study suggested that 4 weeks of PBT did not significantly improve the CMJ and SJ of athletes ( Kovacevic et al, 2022 ). However, the results of the present study were different; after 4 weeks of training, the participants’ CMJ in the APRE group was significantly improved.…”
Section: Discussionmentioning
confidence: 99%